REINFORCING TB-SENSITIVE COMMUNITIES: IMPLEMENTING CADRE TRAINING AS A COMMUNITY BASED PREVENTION AND CONTROL STRATEGY THROUGH INCREASED KNOWLEDGE AND PREPAREDNESS - Dhina Widayati; Ali Muthahhari Rahim; Anisa Catur Wijayanti; Frieda Ani Noor; Ida Zuhroidah; Doa'a Al-Ramlawi; Mericio De Castelho; Eti Poncorini Pamungkasari; Ika Sumiyarsi Sukamto (Universitas Airlangga, 2026)
Introduction: The TB-sensitive communities emphasize the role of cadres as the spearhead of TB prevention and control at the community level. Capacity building for cadres through training is a crucial strategy to strengthen their knowledge and preparedness for early detection and education. This activity aims to analyze the impact of cadre training on the knowledge and preparedness of TB cadres in the Pucang Sawit Community Health Center area in Surakarta. Methods: The activity carried out at Pucang Sawit Community Health Center, Surakarta involved 40 cadres obtained through purposive sampling. The cadre training intervention combines basic education about TB and simulation of the use of flipcharts as a medium for counseling. The training includes the provision of interactive materials, flipchart demonstrations, and role plays to practice communication and education techniques to the community. Evaluation of knowledge and preparedness is carried out through a pretest–posttest using a questionnaire. Results: The training successfully improved cadre knowledge, the majority of respondents were in the medium category (55%) to the majority of respondents being in the high category (72.5%). There was an increase in the preparedness of cadres from the majority being in the poor prepared category (47.5%) to the majority of cadres being in the good category (62.5%). Conclusion: The training contributed to improving cadres’ literacy and preparedness to carry out their TB education and monitoring roles in the community. Preparedness classifications indicated that more than half of the cadres had acquired the basic skills to carry out community tasks, although the proportion who were not ready still required further mentoring. KEYWORDS cadre training; community; empowerment; knowledge; tuberculosis